SEASONAL VARIATION IN THE BIOCHEMICAL COMPOSITION OF FRESHWATER CATFISH WALLAGO ATTU (HAMILTON) IN RELATION TO SEX AND MATURITY CYCLE - SHENDGE, A.N.; PAWAR, B.A.; PANDARKAR, A.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The common freshwater catfish, Wallago alto (Hamilton) from Pune District in Maharashtra State was studied for seasonal variation in its biochemical composition. A significant variation was observed in the body protein and lipid. The data was correlated with the reproductive cycle.